Contract Structure, Time Preference, and Technology Adoption - Shyamal Chowdhury; Joeri Smits; Qigang Sun (Institute of Labor Economics (IZA), 2020)
Do constraints to technology adoption vary by behavioral traits? We randomize 150 villages in Bangladesh into being offered standard microcredit, loans with a grace period, the choice between those two contracts, and control. No discernible average effects are detected on the adoption of mechanized irrigation, hybrid seeds, and chemical fertilizers. However, credit access enhances technology adoption among present-biased farmers, whose output and profits increase. These effects are driven by the standard contract and choice villages, as present-biased farmers select out of the grace period contract. This suggests offering commitment and screening applicants on present bias to enhance agricultural technology adoption.
Keywords: D15; G51; O13; O33; Q14; Q16; 330; microfinance; technology adoption; time inconsistency; Bangladesh